Virtual reality and collaborative learning: a systematic literature review - van der Meer, Nesse; van der Werf, Vivian; Brinkman, Willem-Paul; Specht, Marcus (Frontiers in Virtual Reality, 2023)
Background. While research on Virtual Reality’s potential for education continues to advance, research on its support for social learning is small in scope. With remote collaboration and distance learning becoming increasingly relevant for education (especially since the COVID-19 pandemic), an understanding of Virtual Reality’s potential for Collaborative Learning is of importance. To establish how this immersive technology can support and enhance collaboration between learners, this systematic literature review analyses scientific research on Virtual Reality for Collaborative Learning with the intention to identify (1) skills and competences trained, (2) domains and disciplines addressed, (3) systems used and (4) empirical knowledge established. Method. Two scientific databases were used. Following the PRISMA method, a total of 139 articles were analyzed. A taxonomy was used to classify these articles. Several coders were used for assessing reliability. Results. Based on the literature reviewed, skills and competences developed are divided into five categories. Educational fields and domains seem interested in Virtual Reality for Collaborative Learning because of a need for innovation, communities and remote socialization and collaboration between learners. Systems primarily use monitor-based Virtual Reality and mouse-and-keyboard controls and little state-of-the-art. A general optimism is visible regarding the use of Virtual Reality to support and enhance Collaborative Learning. Furthermore, five distinct affordances of Virtual Reality for Collaborative Learning are identified. Conclusion. Reviewed literature suggests Virtual Reality to be an effective tool for the support and enhancement of Collaborative Learning, though further research is necessary to establish pedagogies.